La posture professionnelle : entre corps propre et corps sociaux - Sylvain Starck
Adopt a professional posture at work seems to be a common social expectation today. So, it is common to think that working competently needs a professional posture. But, when we try to explore its nature or its construction, many questions appear. These reflexions aim to pursue the theorizing of the posture at work from three theoretical frameworks: phenomenology, clinic of activity and theory of social fields. We suggest to understand the posture as a manifestation of the own-body, at the junction of ways of perceiving and behaving socially oriented, which involves intimately the person. Next, we refer to three field researches to analyse the economy of the posture. Finally, we examine the scientific posture which is here a posture on the posture.